Le pubblicazioni dell'Istituto per l'Europa orientale Catalogo storico (1921-1944) - Mazzitelli, Gabriele (Biblioteca di Studi Slavistici, 2016)
With the additional help of archival material, the first part of this volume reconstructs the history of the Institute for Eastern Europe (Ipeo), founded in Rome in 1921, whose activity was characterized by a remarkable editorial production closely connected to the birth and development of Italian Slavic Studies. Despite the inevitable coexistence with fascism and the submission, somehow, to a line of conduct which especially in the 1930s accompanied the regime's policy, the Ipeo's activity was marked above all by a sincere desire to spread knowledge of a world which was still quite unknown in the Italian context under many aspects. The Ipeo operated until the end of World War II, when the government funding and even the political and cultural assumptions which had favoured its birth ceased because of the changed geopolitical context, determined by the end of the conflict. The second part of the volume covers the General alphabetical catalogue of all Ipeo's publications, accompanied by a Chronological catalogue and by an Index of authors, editors, translators and preface writers.